Analytic functions over valued fields - R. Bhaskaran; V. Karunakaran (International Journal of Mathematics and Mathematical Sciences)
Let K be a non-archimedean, non-trivially (rank 1) valued complete field. B, B0 denote the closed and open unit ball of K respectively. Necessary and sufficient conditions for analytic functions defined on B, B0 with values in K to be injective, necessary and sufficient conditions for fixed points, the problem of subordination are studied in this paper.